Ralationship Between the Selected Factors and Academic Achievement of Undergraduate Students of Punjab Agricultural University, Ludhiana - Johal, Khushwant; Dhillon, D.S.; Kumar, Kuldip (Indian Journal of Extension Education, 2010)
The study was undertaken to know the factors affecting the academic achievement of undergraduate students of Punjab Agricultural University, Ludhiana. The study was conducted in the three constituent colleges of PAU, Ludhiana Viz. College of Agriculture, College of Agricultural Engineering, and College of Home Science. The respondents were the students who were enrolled for graduation programme during the academic year 2002- 03 and were in the final year of B.Sc. Agri. (Hons.), B. Tech (Agri. Engg.) and B.Sc. Home Sci. (Hons.). Majority of the students (41.91%) attained poor level of academic achievement. Family income did not influence the academic achievement of the students. There was significant and positive relationship between the living conditions of hostlers as well as day scholars and their academic achievement. The participation of students in co-curricular activities did not influence their academic achievement. The academic achievement was significantly affected in a positive manner by the study habits of students and the academic achievement was found to be independent of the level of adjustment in the college. In order to improve academic achievement, there should be more emphasis on practical work, discussion rather than dictation, more seminars and debates should be organized and internship should be introduced at the end of degree programme.